Pollution, green union, and network industry - Fanti, Luciano; Buccella, Domenico (Estudios de Economía, 2021)
In a network industry, this paper investigates the impact of network effects on total pollution under the presence of a union interested to “local” environmental damages (e.g., polluting production processes damaging workers’ health and the local environment where workers live). Under monopoly, it is shown that, on the one hand, network effects tend to increase the investments in the cleaning technology but, on the other hand, increase the polluting output; consequently, the effects on the total pollution are ambiguous. We also find that total pollution reduces (increases) with increasing network effects intensity if the market is sufficiently large (small). Moreover, the pollution-reducing result of increasing network effects appears when the existing network effects, the union’s environmental concerns and the technological efficiency are sufficiently large. These findings are qualitatively confirmed under Cournot duopoly, offering empirical, as well as policy, implication